LABOR EDUCATION IN PEDAGOGY - Elmuradova Lola Tojialievna; Ergashova Zuhra Ismatillo kizi (International Journal of Innovations in Engineering Research and Technology, 2021)
For decades, the socio-economic situation in the country has been characterized by a gap between supply and demand in the labor market and in the education system, the requirements of employers and the level of training of specialists, indiscriminate means of achieving their goals for a significant part of young people who grew up in conditions of contradictory, multidirectional influence of the family, school and society.